Some Exact Solutions of Two Fifth Order KdV-type Nonlinear Partial Differential Equations (Journal of Partial Differential Equations, 2020)
We consider the generalized integrable fifth order nonlinear Korteweg-de Vries (fKdV) equation. The extended Tanh method has been used rigorously, by computational program MAPLE, for solving this fifth order nonlinear partial differential equation. The general solutions of the fKdV equation are formed considering an ansatz of the solution in terms of tanh. Then, in particular, some exact solutions are found for the two fifth order KdV-type equations given by the Caudrey-Dodd-Gibbon equation and the another fifth order equation. The obtained solutions include solitary wave solution for both the two equations.
Keywords: 5th order KdV-type equation; extended Tanhmethod; CDG equation; exact solutions; solitary wave solution